Color Stability of Resin Dentures Base after Immersion in Cinnamomum Burmannii Extract and Chlorhexidine Solution - Iin Ventika Sari br Sinuhaji; Ricca Chairunnisa; Chaimongkon Peampring (Dentika: Dental Journal, 2024)
Heat cured acrylic resin is a widely known dentures base material, which is often cleaned using Cinnamomum burmannii. Therefore, this study aims to determine the effect of soaking heat cured acrylic resin dentures base on color stability. The study procedures were carried out using a laboratory experimental method with pretest and posttest control group design. The test samples comprised 24 heat cured acrylic resins divided into 6 groups, namely soaking in Cinnamomum burmannii 20%, chlorhexidine 0.2%, and distilled water for 1 and 2 years. Color stability assessement was then carried out using a colorimeter. The results showed that the average color change in the samples after soaking in Cinnamomum burmannii 20% for 1 year was 2.12 and 2.20 for 2 years. Meanwhile, the average color change after being soaked in chlorhexidine was 2.53 and 3.05 after 1 and 2 years, respectively. The results of One-way Analysis of Variance (ANOVA) showed that soaking the samples in Cinnamomum burmannii 20%, chlorhexidine 0.2%, and distilled water for 1 year and 2 years had a significant effect on color stability. The results of LSD (least significant difference) analysis after 1 year of immersion revealed a significant difference in the effects of soaking in chlorhexidine 0.2% compared to distilled water. After soaking for 2 years, a significant difference was observed in the effects of the treatment groups on color stability.